Sondaże a wynik wyborów - polskie doświadczenia lat 1990 - 2005 - Rachwał, Marcin (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2009)
The objective of this paper is to determine the role of opinion polls in voters’ decision making. The fundamental problem is whether the polls reflect the voters’ opinions or rather shape them. The paper also touches upon the prohibition publish the results of the polls before the elections. These considerations take into account the experience of parliamentary and presidential elections in Poland in 1990–2005.
Opinion Polls versus Elections Results - Polish Experience of 1990 - 2005
Keywords: polskie wybory; sondaże